Teologi Moral Paulus dan Krisis Etika Kontemporer: Studi Biblika Roma 12:1–2 dalam Mereduksi degradasi Moralitas - Andreas Eko Nugroho (Sekolah Tinggi Teologi Nusantara, 2026)
The increasingly widespread moral decline in modern society points to an ethical crisis resulting from the weakening of spiritual values, moral relativism, and the rise of individualism, all of which affect the lives of believers. This study aims to analyse the moral theology of the Apostle Paul in Romans 12:1–2 and its relevance in mitigating contemporary moral decline through the ministry of the church. The study employs a qualitative method with a biblical studies approach through exegetical and hermeneutical analysis of Romans 12:1–2. The findings indicate that the concepts of the offering of one’s life and the renewal of the mind form the foundation of Paul’s moral theology, guiding believers to live distinctively from the world’s ways; thus, they hold significant relevance for ministry in shaping the moral character of the congregation amidst the ethical crisis of contemporary society. The novelty of this research lies in its attempt to examine Romans 12:1–2 exegetically whilst linking it to ministry strategies aimed at reducing the decline in morality within modern church communities.AbstrakDegradasi moral yang semakin meluas dalam masyarakat modern menunjukkan adanya krisis etika akibat melemahnya nilai-nilai spiritual, relativisme moral, dan berkembangnya individualisme yang memengaruhi kehidupan orang percaya. Penelitian ini bertujuan menganalisis teologi moral Rasul Paulus dalam Surat Roma 12:1–2 serta relevansinya dalam mereduksi degradasi moralitas kontemporer melalui pelayanan gereja. Penelitian menggunakan metode kualitatif dengan pendekatan studi biblika melalui analisis eksegetis dan hermeneutik terhadap Roma 12:1–2. Hasil penelitian menunjukkan bahwa konsep persembahan hidup dan pembaruan budi menjadi dasar teologi moral Paulus yang menuntun orang percaya hidup berbeda dari pola dunia, sehingga memiliki relevansi penting bagi pelayanan dalam membentuk karakter moral jemaat di tengah krisis etika masyarakat kontemporer. Kebaruan penelitian ini terletak pada upaya mengkaji Roma 12:1–2 secara eksegetis sekaligus menghubungkannya dengan strategi pelayanan dalam mereduksi degradasi moralitas dalam komunitas gereja modern. Kata Kunci: Teologi Paulus, Etika Kristen, Roma 12:1–2, Moral.